2020
DOI: 10.1371/journal.pone.0242424
|View full text |Cite
|
Sign up to set email alerts
|

Statin adherence is lower in primary than secondary prevention: A national follow-up study of new users

Abstract: Background Maintaining adherence to statins reduces the risk of an initial cardiovascular disease (CVD) event in high-risk individuals (primary prevention) and additional CVD events following the first event (secondary prevention). The effectiveness of statin therapy is limited by the level of adherence maintained by the patient. We undertook a nationwide study to compare adherence and discontinuation in primary and secondary prevention patients. Methods Dispensing data from New Zealand community pharmacies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
3
11
0
1
Order By: Relevance
“…LDL-C reduction with statins has been a popular therapy for CVD prevention because statin treatment leads to reduced serum levels of total cholesterol, LDL-C, and triacylglycerols [27,28]. The significance of statins was recognized in the primary and secondary prevention of atherosclerotic CVDs [28][29][30][31][32][33]. In primary prevention, statins substantially decrease CVD morbidity, but only moderately reduce CVD mortality [27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LDL-C reduction with statins has been a popular therapy for CVD prevention because statin treatment leads to reduced serum levels of total cholesterol, LDL-C, and triacylglycerols [27,28]. The significance of statins was recognized in the primary and secondary prevention of atherosclerotic CVDs [28][29][30][31][32][33]. In primary prevention, statins substantially decrease CVD morbidity, but only moderately reduce CVD mortality [27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of statins was recognized in the primary and secondary prevention of atherosclerotic CVDs [28][29][30][31][32][33]. In primary prevention, statins substantially decrease CVD morbidity, but only moderately reduce CVD mortality [27][28][29][30][31][32][33]. Statin use for primary prevention can be effective for individuals at high risk of CVD [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greatest success in maintaining statin therapy occurs in patients with established atherosclerotic disease. 39 Moreover, these patients are commonly followed by specialists who are well informed in the details of statin therapy.…”
Section: For Statin Intolerance In Patients With Clinical Atherosclerotic Disease Maximize Ldl Loweringmentioning
confidence: 99%
“…In New Zealand, adherence to statin over the 3 years after an Acute Coronary Syndrome (ACS) was found to be 66%, although it was 82% for those on a statin prior to ACS admission [ 19 ]. In primary prevention in New Zealand, statin adherence in the first year after initiation of treatment was found to be 63% [ 20 ]. A US study found non-adherence to statin to be as high as 56.0% for secondary prevention patients and 56.4% for primary prevention patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%